New data on the Iberian endemic bee genus Flavipanurgus Warncke Hymenoptera: Apoidea: Andrenidae): Ecological and genomic data reveal a hidden species - Cross, Ian; Wood, Thomas J. (Zootaxa, 2018)
Flavipanurgus is a small genus of panurgine bees known only from the Iberian Peninsula. Despite its status as one of the few bee genera endemic to Europe, Flavipanurgus are poorly represented in collections and until recently, their ecology had been almost unknown. Flavipanurgus ibericus (Warncke, 1972) was described from southern Iberia, with a northern subspecies F. i. kastiliensis (Warncke, 1987) later described from the north. Recent collections in Portugal have revealed clear differences in the pollen collecting patterns of the two taxa, with southern females collecting exclusively from Jasione montana and northern females from Sedum species. In combination with this ecological difference, COI and 28S barcode data indicate that Flavipanurgus kastiliensis stat. nov. should be raised to full species status. The male of Flavipanurgus ibericus s. str. is described for the first time, and updated keys to Flavipanurgus species are provided. Flavipanurgus fuzetus Patiny, 1999 is recorded for the first time from Spain. Further significant records and new floral associations for Flavipanurgus are also presented.